Literacy Socialization Increases Interest in Reading and Public Speaking of Students of Tasikapa Elementary School: Indonesia - Mariano Fay, David; Yohana Fransiska Medho (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
The ability to read and write among the public is crucial to improving the quality of human resources, especially in this age of globalization and fierce competition. The low interest in reading among elementary school students is one of the problems that needs to be addressed immediately, as this has a negative impact on their critical thinking, writing and information comprehension skills. This service program aims to improve students' literacy skills through the establishment and management of Taman Baca around SDN Tasikapa. The approach used includes counseling and mentoring on the importance of literacy, as well as reading education and training aimed primarily at students of SDN Tasikapa. In addition, this program seeks to increase interest in reading by optimizing the use of school library facilities. Through this activity, it is hoped that students can have a deeper understanding of the importance of reading, so that a culture of literacy can continue to be strengthened in the school environment and also in the village community in a sustainable manner